1998
DOI: 10.2337/diacare.21.5.841
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocyst(e)inemia and Endothelial Dysfunction in IDDM

Abstract: Hyperhomocyst(e)inemia is common in nephropathic diabetic patients and may contribute to the enhanced morbidity and mortality from cardiovascular diseases characteristically observed in IDDM patients with diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
97
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 52 publications
6
97
0
1
Order By: Relevance
“…Several studies have demonstrated that Hcy levels are increased in diabetes. Elevated Hcy levels were shown to be a stronger risk factor in diabetics than in non-diabetic patients (1,19,20,21,24,29,30). Plasma Hcy levels were also found to be significantly elevated in our type 2 diabetic patients with atherosclerotic vascular disease when compared with patients without vascular disease.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Several studies have demonstrated that Hcy levels are increased in diabetes. Elevated Hcy levels were shown to be a stronger risk factor in diabetics than in non-diabetic patients (1,19,20,21,24,29,30). Plasma Hcy levels were also found to be significantly elevated in our type 2 diabetic patients with atherosclerotic vascular disease when compared with patients without vascular disease.…”
Section: Discussionmentioning
confidence: 49%
“…Hcy levels were found to be elevated in patients with vascular disease and were proposed to contribute to atherosclerosis in patients with coronary artery disease, stroke, and peripheral vascular disease (1,19,20,22,24,28). Hcy-induced vascular pathologies include fragmentation of the internal elastic lamina, disruption of elastic fibers, smooth muscle hyperplasia, and arterial and venous thrombosis (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other risk factors have been recognized, one of them is elevated level of homocysteine [3]. Increasing incidence of vasculopathy and preeclampsia in diabetes mellitus is associated with increased homocysteine level [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…1 Several aminothiols, including homocysteine and cysteine, can promote atherogenesis by virtue of their effects on endothelial function, vascular smooth muscle cell activation and hemostatic activation. [2][3][4][5][6][7][8] These aminothiols have a critical role as intracellular redox buffers, and it is also becoming increasingly recognized that they comprise an important extracellular redox system. 9,10 It has also been reported that homocysteine exerts its detrimental effects in part through a mechanism involving oxidative stress.…”
Section: Introductionmentioning
confidence: 99%